Enhanced expression of an industry applicable CotA laccase from Bacillus subtilis in Pichia pastoris by non-repressing carbon sources together with pH adjustment: Recombinant enzyme characterization and dye decolorization. Issue 1 (January 2015) - Wang, Tian-Nv; Lu, Lei; Wang, Jing-Yao; Xu, Teng-Fei; Li, Jun; Zhao, Min
Graphical abstract